A simulating method of moisture continuous diffusion under changing temperatures and analysis of moisture-induced stresses covering moisture desorption and reflow processes for the QFN. (April 2021) - Shi, Xinghua; Qiu, Yuanying; Jia, Fei; Ma, Hongbo
Abstract: Moisture in the atmosphere could diffuse into plastic packaging devices, which would cause high hygro-mechanical stress and vapor stress and lead irreversible damages. In this paper, an analysis method for moisture continuous diffusion under changing temperature is proposed. Considering the vapor pressure induced strain as hygro-mechanical strain, a corresponding relationship between the parameters of hygro-mechanical stress and vapor stress is built. Subsequently, the formula of moisture-induced total stress is derived according to the superposition principle. A QFN (Quad Flat No‑lead) package model with gold wires inside is established to validate the effectiveness of the method. The moisture continuous diffusion from the absorption process to the desorption one is obtained, then the dynamic variations of the hygro-mechanical stress, vapor stress and moisture-induced total stress of the QFN during the desorption process and the entire reflow process are obtained for the first time ever. The results prove that the method in this paper can be employed for the analysis of moisture diffusion and moisture-induced stress under dynamic temperature and uneven humidity distribution. Highlights: Moisture continuous diffusion simulation under changing temperatures is implemented. An analogy between the hygro-mechanical stress and vapor stress is made. Moisture-induced stresses of the QFN device with gold wires inside is analyzed. Vapor stress and moisture-induced total stress increase sharply with temperature.